2006
DOI: 10.1111/j.1365-2818.2006.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of microband orientation in a commercial purity aluminium alloy subjected to forward and reverse torsion using Electron Backscatter Diffraction (EBSD)

Abstract: SummaryHigh-resolution electron backscatter diffraction has been used to study the effects of strain reversal on the evolution of microbands in commercial purity aluminium alloy AA1200. Deformation was carried out using two equal steps of forward/ forward or forward/reverse torsion at a temperature of 300 ° C and strain rate of 1 s − 1 to a total equivalent tensile strain of 0.5. In both cases, microbands were found in the majority of grains examined with many having microband walls with more than one orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The results presented above have shown that a linear (F/F) torsion test in hot deformed AA5052 produces a strong macroscopic directionality in the microbands formed. The data presented here also corresponds nearly exactly with the data of Lopez-Pedrosa et al [8] for AA1200 deformed at the same temperature to the same strain and the data of Hughes and Hansen [9], for room temperature deformed nickel deformed to slightly lower strain levels. This would suggest that like other deformation modes the microband angle distribution for torsion is very similar for both hot and cold deformation and materials of similar stacking fault energy.…”
Section: Discussionsupporting
confidence: 90%
“…The results presented above have shown that a linear (F/F) torsion test in hot deformed AA5052 produces a strong macroscopic directionality in the microbands formed. The data presented here also corresponds nearly exactly with the data of Lopez-Pedrosa et al [8] for AA1200 deformed at the same temperature to the same strain and the data of Hughes and Hansen [9], for room temperature deformed nickel deformed to slightly lower strain levels. This would suggest that like other deformation modes the microband angle distribution for torsion is very similar for both hot and cold deformation and materials of similar stacking fault energy.…”
Section: Discussionsupporting
confidence: 90%
“…After reversal of the strain path in tension/compression tests [10], as well as in reversed torsion tests [11], the distribution of dislocation boundary inclination angles resembles a superposition of the distributions observed before and after the strain path reversal.…”
Section: Introductionmentioning
confidence: 74%
“…The apparent contradictory results for local parameters (stagnation) and OS (increase) from a strain of 0.4–0.5 could be associated to the omission of an analysis of the low misorientation axis. Indeed, the progressive alignment of the low misorientation axis with strain according to some external direction (Cizek et al ., 2005; López‐Pedrosa et al ., 2006) could lead to a more efficient way of accumulating misorientation with distance.…”
Section: Discussionmentioning
confidence: 99%